Effects of land cover and soil properties on denitrification potential in soils of two semi-arid grasslands in Inner Mongolia, China - Wu, X.; Liu, G.; Butterbach-Bahl, Klaus; Zheng, X.; Bruggemann, N. (Elsevier, 2013)
High N2O emissions have been observed in semi-arid grasslands, especially during freeze/thaw periods, when denitrification might be the main process of N2O production. However, there have been few denitrification studies in semi-arid grassland. This study was designed to determine the denitrification potential of four representative land cover types (typical steppe, meadow steppe, marshland, arid steppe) in two grasslands in Inner Mongolia, China.We found that soils from different land cover types exhibited significantly different denitrification potentials, with highest rates in marshland and lowest rates in arid steppe. Denitrification potentials were maximal in the upper layer and generally decreased with depth for all soils. Soil water content, soil carbon and nitrogen availability, and C/N ratio were found to be significantly correlated with denitrification potentials in all soils. Addition of glucose or/and nitrate significantly increased denitrification activities throughout the profile for all soils, suggesting that both bioavailable carbon and nitrogen were limiting factors of denitrification in these grasslands soils. However, further field studies are needed to translate the denitrification potentials determined in laboratory measurements to denitrification rates under field conditions.